Volume 4B: Combustion, Fuels and Emissions 2014
DOI: 10.1115/gt2014-26376
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Flame Stabilization in a High-Pressure Multi-Jet Combustor by Laser Measurement Techniques

Abstract: In this contribution, comprehensive optical and laser based measurements in a generic multi-jet combustor at gas turbine relevant conditions are presented. The flame position and shape, flow field, temperatures and species concentrations of turbulent premixed natural gas and hydrogen flames were investigated in a high-pressure test rig with optical access. The needs of modern highly efficient gas turbine combustion systems, i.e., fuel flexibility, load flexibility with increased part load capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…6 of Ref. 13. This leads to an intense mixing of burnt gas with fresh fuel/air mixtures, and thus stabilization of the flame.…”
Section: Introductionmentioning
confidence: 98%
“…6 of Ref. 13. This leads to an intense mixing of burnt gas with fresh fuel/air mixtures, and thus stabilization of the flame.…”
Section: Introductionmentioning
confidence: 98%
“…The turbulent high speed pipe flow inside these nozzles provides sufficient premixing and high flashback resistance at a wide range of operation conditions and fuels. Previous research demonstrated operation with pure hydrogen is possible at gas turbine relevant conditions with low NO x emissions and without flashback [7,8]. A key feature of a FLOX ® burner is the large inner recirculation zone, which brings hot burnt gas back to the combustor nozzles, where it supports the ignition of the incoming high momentum jet of fresh unburned fuel/air mixture.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest model combustor is a lab-scale single nozzle burner, that has extensively been investigated at atmospheric conditions, both experimentally [11,12] and numerically [13]. Furthermore, a 3-nozzle model combustor has been investigated at high pressure [8]. All of these model combustors were down-scaled compared to full size gas turbine combustors, and therefore it was challenging to perform measurements with sufficient spatial resolution in order to resolve structures in context of flame stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…This injector configuration is similar to the FLOX V R combustion experiments, which have been widely studied. 34,41,42 The combustion chamber has cross-section dimensions of 238 mm and 30 mm in the x-and z-directions, respectively. In the flow (y-) direction, the crosssectional area is constant for the first 115 mm and is followed by a 92 mm long converging section where the chamber aspect ratio is held constant.…”
Section: Combustor Designmentioning
confidence: 99%
“…This injector configuration is similar to the FLOX® combustion experiments, which have been widely studied. 34,41,42…”
Section: Experiments Descriptionmentioning
confidence: 99%